PENERAPAN AUDIT KEPUASAN KINERJA KARYAWAN BAGIAN PENJUALAN DI PT WENDYâS TRANS BURGER SURABAYA - Arifiyanto, Gatot (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purposes of this research are: (1) to assess the implementation of employeesâ performance satisfaction audit in the sales department at PT Wendyâs Trans Burger Surabaya; (2) to analyze and to find out the performance satisfaction of human resources to the sales at PT Wendyâs Trans Burger Surabaya. It can be concluded from the result of the research that the employeesâ performance satisfaction at PT Wendyâs Trans Burger Surabaya has been running well but the recruitment procedure of new labor particularly the job vacancy information its range should be widened. The performance assessment system should not only rely on attendance discipline but it is necessary to have additional assessment i.e. performance assessment. Moreover, the attendance procedure should use fingerprint system or identity card so the performance of the employees can run maximally.Keywords: Management Audit, Employeesâ Performance Satisfaction.